Sherris Medical Microbiology An introduction to infectious diseases - Ryan, Kenneth J Ray, C. George (McGraw-Hill, 2004)
Thoroughly revised and updated, this book provides students with a solid grasp of etiologic agents, pathogenic processes, epidemiology, and the basis of major therapy. Includes complete discussions of the major bacterial, viral, fungal, and parasitic pathogens. Highlighted marginal notes and clinical applications are included throughout.